Oral manifestation associated with avelumab - Kevin Chung; Annu Singh; Joseph M. Huryn; Cherry L. Estilo (Oral Oncology Reports)
Emerging immunotherapies are becoming more prominent in treating various cancers. However, side effects and toxicities can induce systemic and oral manifestations which can be debilitating and negatively affect a patient’s quality of life. Avelumab is a relatively recent immunotherapy drug that is used in the treatment of both renal and metastatic urothelial carcinomas. However, oral manifestation, to the best of our knowledge, has not been reported in the literature in association. The purpose of this case report is to describe an oral manifestation associated with avelumab, and subsequent management to obtain resolution of symptoms.